1977
DOI: 10.1115/1.3446500
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Existing Two-Phase Flow Correlations for Use With ASME Sharp Edge Metering Orifices

Abstract: The two-phase flow correlations developed by Murdock, James, Marriott, and Smith and Leang are evaluated for the case of flow through sharp edge measuring orifices which physically meet ASME standards for flow measurement. The evaluation is based on two sets of consistent orifice flow data. The first data base consists of 34 test points for the flow of steam-water mixtures. The second data base consists of 81 data points for the flow of air-water, natural gas-water, natural gas-salt water, and natural gas-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Stewart et al [25,26] reported that the ε of a V-Cone meter with the constant β is independent of Re and dependent on the DP ( P), the operating pressure (P) and the isentropic exponent (κ). ε has the form given in equation (10). Moreover, studies also show that C d slightly increases with Re with other parameters kept constant [29].…”
Section: Effects Of Parametersmentioning
confidence: 89%
See 1 more Smart Citation
“…Stewart et al [25,26] reported that the ε of a V-Cone meter with the constant β is independent of Re and dependent on the DP ( P), the operating pressure (P) and the isentropic exponent (κ). ε has the form given in equation (10). Moreover, studies also show that C d slightly increases with Re with other parameters kept constant [29].…”
Section: Effects Of Parametersmentioning
confidence: 89%
“…partial separation, isokinetic sampling, vortex meters and ultrasonic meters) are available to meter the wet gas, the majority of wet gas meter designs employ the differential pressure (DP) meter technology including the orifice plate, the Venturi and V-Cone meter [5]. Many investigators such as Murdock [6], Chisholm [7,8], Smith and Leang [9,10], Lin [11], de Leeuw [12], Steven and Stewart [13][14][15][16] and Dong [17,18] have explored the DP devices in wet gas (in fact, some of their testing conditions were beyond the range of wet gas flow). They found that DPbased flow meters shared many performance characteristics in wet gas applications.…”
Section: Introductionmentioning
confidence: 99%